A Rare Radiologic Finding of Type III Unilateral Styloid Process Elongation in Dental Panoramic Radiograph: A Case Report and Short Review - Diba, Silviana Farrah; Yanuaryska, Ryna Dwi; Istadi, Didit; Verisandri, Aufa Lufhf Ambar (European Journal of General Dentistry, 2025)
The styloid process (SP) is a pointed component of the temporal bone that protrudes downward toward the front. If its length exceeds 30 mm, it is considered elongated, and there is a possibility that it will cause symptoms or be asymptomatic. In general, panoramic radiography helps identify the type of SP elongation. The objective of this case report was to demonstrate the rare finding of type III unilateral SP elongation on a panoramic radiograph and to provide a short review of various case reports on this topic. A 61-year-old female patient presented to our hospital with the chief complaint of right facial swelling extending to the ear. The patient experienced persistent swelling and pain for 3 months. Panoramic radiography revealed a 65.06-mm elongation of the right SP consisting of three fragments, classified as type III based on the Langlais classification. Additionally, a fracture-like appearance was observed in the head of the right condyle. Additional diagnostic procedures, including fine-needle aspiration biopsy and computed tomography of the head, confirmed the presence of swollen parotid glands, leading to the diagnosis of parotitis. Type III SP elongation could be clearly observed on a panoramic radiograph. As this is a rare radiographic finding, it is necessary for the clinician to recognize bone morphology abnormalities that appear on panoramic radiographs to identify this condition.
Keywords: styloid process; calcifications; elongated styloid process; Eagle's syndrome; panoramic radiograph